Analisis Pelaksanaan Perhitungan dan Pembagian SHU Pada KPRI SMADA Palangka Raya - Noor Anisa; Dehen Erang; Windy Utami Putri (FKIP, Universitas Palangka Raya, 2023)
Analysis of the Implementation of Calculation and Distribution of SHU at KPRI SMADA at SMA Negeri 2 Palangka Raya. The location of this research is KPRI SMADA SMA Negeri 2 Palangka Raya which is located at Jalan K.S. Tubun No.02 Pahandut, Palangka Raya City. This cooperative was formed on January 25, 1988 with a cooperative legal entity No: 1057/BH/XIX/1989. This thesis was written with the aim of knowing the implementation of the calculation and distribution of SHU in the KPRI SMADA Cooperative in 2021; and to find out the distribution of SHU KPRI SMADA in 2021 in accordance with the provisions in the AD/ART KPRI SMADA SMA Negeri 2 Palangka Raya. This study uses a descriptive qualitative approach, this type of research uses a document studies, data collection methods used are documentation, interviews, and observation, and the data obatined is analyzed using the profit an loss formula. Based on the results of the study, it is known that the calculation and distribution of the remaining operating results (SHU) of KPRI